A mathematical framework for predicting thermal damage during bone electrostimulation. Issue 4 (6th July 2015) - Carlos F.R. Lemos Antunes, Professor; Vanegas-Acosta, Juan C.; Lancellotti, V.; Zwamborn, A.P.M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Electric fields (EFs) are known to influence cell and tissue activity. This influence can be due to thermal or non-thermal effects. While the non-thermal effects are still matter of discussion, thermal effects might be detrimental for cell and tissue viability due to thermal damage, this fact being exploited by applications like hyperthermia and tissue ablation. The paper aims to discuss these issues. Design/methodology/approach – In this work the authors investigate the influence of thermal damage in the consolidation of bone formation during electrostimulation (ES). The authors introduce a mathematical model describing the migration of osteoprogenitor cells, the thermal variation, the thermal damage accumulation and the formation of new bone matrix in an injury (fracture) site. Findings – Numerical results are in agreement with experimental data and show that EFs more intense than 7.5 V/cm are detrimental for the viability of osteoprogenitor cells and the formation of new bone. Originality/value – The model is suitable to conduct dosimetry studies in support of other different ES techniques aimed at improving bone and soft tissues repair.